Conformations of cationized linear oligosaccharides revealed by FTMS combined with in‐ESI H/D exchange. (20th August 2015) - Kostyukevich, Yury; Kononikhin, Alexey; Popov, Igor; Nikolaev, Eugene
<x xml:space="preserve">Abstract</x> Previously (Kostyukevich et al. Anal Chem 2014, 86, 2595), we have reported that oligosaccharides anions are produced in the electrospray in two different conformations, which differ by the rate of gas phase hydrogen/deuterium (H/D) exchange reaction. In the present paper, we apply the in‐electrospray ionization (ESI) source H/D exchange approach for the investigation of the oligosaccharides cations formed by attaching of metal ions (Na, K) to the molecule. It was observed that the formation of different conformers can be manipulated by varying the temperature of the desolvating capillary of the ESI interphase. Separation of the conformers was performed using gas phase H/D approach. Because the conformers have different rates of the H/D exchange reaction, the deuterium distribution spectrum becomes bimodal. It was found that the conformation corresponding to the slow H/D exchange rate dominates in the spectrum when the capillary temperature is low (~200 °C), and the conformation corresponding to the fast H/D exchange rate dominates at high (~400 °C) temperatures. In the intermediate temperature region, two conformers are present simultaneously. It was also observed that large oligosaccharide requires higher temperature for the formation of another conformer. It was found that the presence of the conformers considerably depends on the solvent used for ESI and the pH. We have compared these results with the previously performed in‐ESI source H/D exchange experiments with peptides and proteins. Copyright © 2015 John Wiley & Sons, Ltd.